The intricate relationship between technology, knowledge and creativity - Hafizoah, Kassim (Pejabat Naib Canselor, 2014)
Ten years - yes, a decade. This is the amount of time needed by an individual o construct and gather extensive domain specific knowledge and measured practice for successful creative productions. This ten-year rule was introduced by John R Hayes, a creativity theorist, in 1989 to discuss his studies on creative process where he exemplified the likes of Newton and Mozart. These creative individuals spent years learning, networking, researching and practicing to finally produce their notable works.